Anticorpos IgY policlonais anti-fosfolipase A2: ferramenta auxiliar para o estudo da ação anti-parasitária - Borges, Isabela Pacheco (2019)
Activities of phospholipases (PLAs) have been linked to pathogenesis in various microorganisms. These are involved in processes of cell invasion, virulence, survival and remodeling / modification of the host cell phospholipid composition so the interest in these enzymes as potential targets that could contribute to the control of parasite survival and proliferation. Chicken eggs immunized with BnSP-7, a Lys49 phospholipase A2 (PLA2) homologue from Bothrops pauloensis snake venom, represent an excellent source of polyclonal antibodies with potential inhibitory activity on parasite PLAs. Herein, we report the production, characterization and anti-parasitic effect of IgY antibodies from egg yolks of hens immunized with BnSP-7. Produced antibodies presented increasing avidity and affinity for antigenic toxin epitopes throughout immunization, attaining a plateau after 4 weeks. Pooled egg yolks-purified anti-BnSP-7 IgY antibodies were able to specifically recognize different PLA2s from Bothrops pauloensis and Bothrops jararacussu venom. Antibodies also neutralized BnSP-7 cytotoxic activity in C2C12 cells. In addition, the antibodies recognized targets in Leishmania (Leishmania) amazonensis and Toxoplasma gondii extracts by ELISA and immunofluorescence assays. Anti-BnSP-7 IgY antibodies were cytotoxic to T. gondii tachyzoites and L. (L.) amazonensis promastigotes were able to decrease the proliferation of both parasites treated prior to infection and inhibit the invasion of promentigotes forms of L. (L.) amazonensis. Finally, anti-BnSP-7 antibodies were used to construct a nanocomposite modified graphite immunosensor, that could detect BnSP-7 and targets in L. (L.) amazonensis extract. These data suggest that anti-BnSP-7 IgY is an important tool for discovering new parasite targets, blocking parasitic effects and serving as a diagnostic tool.